(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The research intended to examine the racial quota system and its adoption by universities, based on its historical context, as well as due to the need for this proposal for the evolution of Brazil, as a Democratic State of Law, whose pillars are citizenship and dignity of human person. Therefore, this study aimed to investigate the role of racial quotas as an affirmative action to achieve the fundamental right to education and as a form of historical, social, cultural and economic reparation and, especially, as a tool to combat structural and promoting the belonging of black people to spaces of power and decision-making. To this end, data collected by IBGE, INEP and ABNP were analyzed, which demonstrated the effectiveness of the Quota Law, for the admission of the black population to universities, as well as the significant impact after the pandemic. It is concluded that, despite the impacts of the pandemic on the entry of black people into higher education, education is still a mechanism for breaking racist cultural paradigms and an effective measure to reduce poverty and marginalization, as it enables black people to belong in spaces of power. The study was supported by qualitative bibliographic research in Laws, scientific articles, books, institutional websites and other documents that guided a hypothetical-deductive analysis.